Phase and amplitude of ecosystem carbon release and uptake potentials as derived from FLUXNET measurements - Falge, E.; Tenhunen, J.; Baldocchi, D.; Aubinet, M.; Bakwin, P.; Berbigier, Paul; Bernhofer, C.; Bonnefond, J.M.; Burba, G.; Clement, R.; Davis, K.J.; Elbers, J.A.; et al. (Agricultural and Forest Meteorology, 2002)
International audience As length and timing of the growing season are major factors explaining differences in carbon exchange of ecosystems. we analyzed seasonal patterns of net ecosystem carbon exchange (F-NEE) using eddy covariance data of the FLUXNET data base (http://www-eosdis.ornl.gov/FLUXNET). The study included boreal and temperate. deciduous and coniferous forests, Mediterranean evergreen systems, rainforest, native and managed temperate grasslands, tundra, and C-3 and C-4 crops. Generalization of seasonal patterns are useful for identifying functional vegetation types for global dynamic vegetation models, as well as for global inversion studies, and can help improve phenological modules in SVAT or biogeochemical models. The results of this study have important validation potential for global carbon cycle modeling. The phasing of respiratory and assimilatory capacity differed within forest types: for temperate coniferous forests seasonal uptake and release capacities are in phase, for temperate deciduous and boreal coniferous forests, release was delayed compared to uptake. According to seasonal pattern of maximum nighttime release (evaluated over 15-day periods. F-max) the study sites can be grouped in four classes: (1) boreal and high altitude conifers and grasslands: (2) temperate deciduous and temperate conifers; (3) tundra and crops; (4) evergreen Mediterranean and tropical forest,,, Similar results are found for maximum daytime uptake (F-min) and the integral net carbon flux, but temperate deciduous forests fall into class 1. For forests, seasonal amplitudes of F-max and F-min increased in the order tropical < Mediterranean and temperate coniferous < temperate deciduous and boreal forests, and the pattern seems relatively stable for these groups. The seasonal amplitudes of F-max and F-min are largest for managed grasslands and crops. Largest observed values of F-min varied between -48 and -2 mumol m(-2) s(-1), decreasing in the order C-4-crops > C-3-crops > temperate deciduous ...